Multiple exchange processes on mineral surfaces control the transport of dissolved organic matter through soil profiles. (March 2018) - Leinemann, T.; Preusser, S.; Mikutta, R.; Kalbitz, K.; Cerli, C.; Höschen, C.; Mueller, C.W.; Kandeler, E.; Guggenberger, G.
Abstract: Organic topsoil layers are important sources of dissolved organic matter (DOM) transported to deeper soil layers. During passage through the mineral soil, both organic matter (OM) quality and quantity change markedly. Whether these alterations are due to sorption processes alone or to additional stepwise exchange processes of OM on mineral surfaces ("cascade model") is not fully understood. To test the "cascade model", we conducted a laboratory flow cascade experiment with undisturbed soil columns from three depths of two different soil profiles (Dystric and Eutric Cambisol) using carbon (C) isotope labelling. Each of the connected topsoil and subsoil columns contained a goethite (α-FeOOH) layer either with or without sorbed 13 C-labelled OM to assess the importance of OM immobilization/mobilization reactions with reactive soil minerals. By using a multiple method approach including 13 C analysis in the solid and solution phases, nanometer scale secondary ion mass spectrometry (NanoSIMS), and quantitative polymerase chain reaction ( q PCR), we quantified organic carbon (OC) adsorption and desorption and net OC exchange at goethite surfaces as well as the associated microbial community patterns at every depth step of the column experiment. The gross OC exchange between OM-coated goethite and the soil solution was in the range of 15–32%. This indicates that a considerable proportion of the mineral associated OM was mobilized and replaced by percolating DOM. We showed that specific groups of bacteria play an important role in processing organic carbon compounds in the mineral micro-environment. Whereas bulk soils were dominated by oligotrophic bacteria such as Acidobacteria, the goethite layers were specifically enriched with copiotrophic bacteria such as Betaproteobacteria . This group of microorganisms made use of labile carbon derived either from direct DOM transport or from OM exchange processes at goethite surfaces. Specific microorganisms appear to contribute to the cascade process of OM transport within soils. Our study confirms the validity of the postulated "cascade model", featuring the stepwise transport of OM within the soil profile. Highlights: Experimental evidence of the "cascade model" of DOM transport is provided. Mineral-associated OM can be replaced by DOM over the whole soil profile. Microbial activity at reactive mineral surfaces is involved in downward cycling of DOM.